IMAGES OF SOCIAL PARTICIPATION IN THE AGENDA OF THE LULA III ADMINISTRATION - Martelli, Carla Giani [UNESP]; Almeida, Carla; Capella, Ana Claudia [UNESP] (Escola Nacl Adm Publica-enap, 2024)
This study aims to analyze how the social participation policy was incorporated into the agenda of Lula III's administration during the transition period, as well as the policy images of participation mobilized in this context. The concept of image is part of agenda-setting and policy formulation theories, which guide the theoretical framework of this work. To understand the image of social participation policy, we focus our attention on the Transition Cabinet (TC), established to plan the strategies of the new government, which would assume the Presidency of the Republic in January 2023. Based on documents and interviews with key actors involved in the TC, the study retrieves different images of social participation in Brazil, from the Constitution of 1988, through the idea of'participation as a method of government' (until 2014), participation as an 'ideological' issue (from 2018 onwards). The analysis of the debates produced during the TC reveals the attempt to build and innovate the image of participation, recognizing previous limitations and facing contemporary political challenges, such as the rise of right-wing movements.
Keywords: social participation; Lula 3 government; public policy image; transition cabinet